Analisis Komprehensif Faktor-Faktor Pemicu Banjir dan Dampaknya terhadap Ketahanan Sosial Ekonomi Masyarakat di Wilayah Lampung - Indah Purwoningsih; Lulu Rintan Apriliyani; Nadia Sabila; Siti Musaroh Maydiana Alpa; Abdul Halim; Berchah Pitoewas (CV. ITTC INDONESIA, 2025)
This study aims to provide a comprehensive analysis of the factors triggering floods and their impacts on the socio-economic resilience of communities in the Lampung region, using a literature review and field observations. The literature review identifies various flood-causing factors, including natural elements such as high rainfall, topography, and river capacity, as well as anthropogenic factors like land use changes, inadequate drainage systems, and human activities that increase flood risk. Field observations complement the literature findings by examining real conditions related to infrastructure, settlement patterns, and the socio-economic impacts of flooding. The analysis reveals that floods in Lampung result from the interaction of natural and human factors, causing significant disruptions to economic activities, health, and community well-being. This study highlights the importance of sustainable environmental management and enhancing community adaptive capacity to strengthen socio-economic resilience against flood disasters in the region.